1998
DOI: 10.1291/hypres.21.1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Induced by Neonatal Monosodium Glutamate Treatment in Spontaneously Hypertensive Rats: An Animal Model of Multiple Risk Factors.

Abstract: The present study was designed to develop an animal model of multiple risk factors, including obesity, hypertension, non-insulin-dependent diabetes mellitus, and hyperlipidemia. Hypothalamic obesity was induced by neonatal monosodium glutamate (MSG) treatment in spontaneously hypertensive rats (SHR). Female newborn SHR were treated intraperitoneally with 2 or 4 mg/kg body weight of MSG for 5 days. Obesity developed in SHR treated with 4 mg/kg of MSG but not in SHR treated with 2 mg/kg of MSG. Obese SHR had imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
2
15
1
6
Order By: Relevance
“…The obesity was not caused by polyphagia. It was said by Iwase et al [3] and Cameron et al [1] that obesity without polyphagia is due to the amount and frequency of MSG injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obesity was not caused by polyphagia. It was said by Iwase et al [3] and Cameron et al [1] that obesity without polyphagia is due to the amount and frequency of MSG injection.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the ventromedial nucleus of the hypothalamus was destroyed by injecting mice with goldthioglucose (GTG) [6,7] and that the injected mice showed polyphagia and obesity [8], thereafter becoming diabetic. On the other hand, there are few reports of injecting MSG into mice that already have a diabetic condition [1,9], and also few reports concerning diabetes in other experimental animals [3,5]. There is no report of ICR normal mice developing obesity without polyphagia and a diabetic condition by injecting MSG, and of the condition continuing over a long period.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, however, has been reported in IRS-1 deficient mice which are insulin resistant but not obese at 5±8 months of age [26]. It is interesting to note that when rats are made obese, either genetically [35] or by hypothalamic damage [36], and mated with spontaneously hypertensive rats, extreme hyperinsulinaemia and glucose intolerance can result but hypertension is not exacerbated [35] and can actually be attenuated [36]. These data illustrate that obese animals do not necessarily have hypertension and that hypertension is not directly related to the level of hyperinsulinaemia (at least in the short-term).…”
Section: Discussionmentioning
confidence: 99%
“…16 Ressalta-se que, em outros estudos da literatura, ratos Wistar são utilizados como controles dos ratos SHR. [17][18][19] Apesar do menor peso corporal verificado no período basal, os ratos WST + MSG e SHR + MSG tiveram, nas 12 semanas do estudo, um percentual maior de ganho de peso em relação aos animais controles. O menor peso inicial dos animais MSG deveu-se provavelmente à ação neurotóxica dessa droga, que determina menor secreção de hormônio do crescimento.…”
Section: Medida Da Obesidade Visceralunclassified